Exploration of Ethnomathematics in Saung Ranggon of Cikedokan Village Cikarang Barat Through Geometry Learning - Fijayanti, Niken; Wahidin, Wahidin (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2023)
ABSTRACT The aims of this study were to (1) understand the concept of geometry with geometric material, (2) understand the concept of geometry with geometric material, (3) understand the concept of geometry with geometric transformation material, and (4) understand the development of numeration contained in the design. Saung Ranggon traditional house. This study is a qualitative research conducted using an ethnographic approach to explore and understand the concept of geometry through the use of geometric materials and geometric transformation materials, as well as the development of numeration within the design of the Saung Ranggon traditional house. The data collection techniques used in this study included interviews, observations, documentation techniques, and data analysis using triangulation techniques with the Spradley model consisting of domain analysis, taxonomic analysis, and component analysis. The results of this study are the geometric concepts contained in the design of the Saung Ranggon traditional house, namely, the concept of a flat shape (a rectangle that can be seen from the door, a square that can be seen from the side wall, a triangle that can be seen from the ventilation section, a trapezoid that can be seen from the back wall, a rhombus that can be seen from the fence section, and circles that can be seen from the old well), the concept of geometric shapes (tubes), the concept of transformation geometry (reflection on the  axis,  axis,  axis), and numeration development are used to solve the cost problem.